Configurations of Capacity for Change in Entrepreneurial Threshold Firms: Imprinting and Strategic Choice Perspectives. (20th February 2015) - Judge, William Q.; Hu, Helen W.; Gabrielsson, Jonas; Talaulicar, Till; Witt, Michael A.; Zattoni, Alessandro; López‐Iturriaga, Félix; Chen, Jean Jingham; Shukla, Dhirendra; Quttainah, Majdi; Adegbite, Emmanuel; Luis Rivas, José; et al.
ABSTRACT Imprinting theory suggests that founding conditions are 'stamped' on organizations, and these imprinted routines often resist change. In contrast, strategic choice theory suggests that the firm can overcome organizational inertia and deliberately choose its future. Both theories offer dramatically different explanations behind an organization's capacity for change. IPO firms provide a unique context for exploring how imprinting forces interact with strategic choice factors to address organizational capacity for change as a firm moves from private to public firm status. Juxtaposing imprinting and strategic choice perspectives, we employ fuzzy set analysis to examine the multi‐level determinants of organizational capacity for change. Our cross‐national data reveal three effective configurations of organizational capacity for change within IPOs, and two ineffective configurations. Our results suggest that the antecedents of organizational capacity for change in entrepreneurial threshold firms are non‐linear, interdependent, and equifinal.